Origin and production of inflammatory perivascular macrophages in pulmonary hypertension. (December 2017) - Florentin, Jonathan; Dutta, Partha
Abstract: Myeloid cells, including monocytes and macrophages participate in steady state immune homeostasis and help mount the adaptive immune response during infection. The function and production of these cells in sterile inflammation, such as pulmonary hypertension (PH), is understudied. Emerging data indicate that pulmonary inflammation mediated by lung perivascular macrophages is a key pathogenic driver of pulmonary remodeling leading to increased right ventricular systolic pressure (RVSP). However, the origin of these macrophages in pulmonary inflammation is unknown. Inflammatory monocytes, the precursors of pathogenic macrophages, are derived from hematopoietic stem and progenitor cells (HSPC) in the bone marrow and spleen during acute and chronic inflammation. Understanding the role of these organs in monocytopoiesis, and the mechanisms of HSPC proliferation and differentiation in PH are important to discover therapeutic targets curbing inflammation. This review will summarize the current limited knowledge of the origin of lung macrophage subsets and over-production of inflammatory monocytes in PH.